2021
DOI: 10.3390/ijms221810166
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Field (GMF)-Dependent Modulation of Iron-Sulfur Interplay in Arabidopsis thaliana

Abstract: The geomagnetic field (GMF) is an environmental factor affecting the mineral nutrient uptake of plants and a contributing factor for efficient iron (Fe) uptake in Arabidopsis seedlings. Understanding the mechanisms underlining the impact of the environment on nutrient homeostasis in plants requires disentangling the complex interactions occurring among nutrients. In this study we investigated the effect of GMF on the interplay between iron (Fe) and sulfur (S) by exposing Arabidopsis thaliana plants grown under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Finally, the molecular and metabolic effects of a MF have started to be studied in plants. Using a near null MF (NNMF), different authors have reported changes at the nutritional level [Narayana et al, 2018; Islam et al, 2020; Vigani et al, 2021], lipid composition [Islam et al, 2020] and gene expression. Interestingly, the speed of these responses suggests a first signaling stage that does not depend on gene expression [Narayana et al, 2018], even though several gene responses have been reported in response to a MF.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the molecular and metabolic effects of a MF have started to be studied in plants. Using a near null MF (NNMF), different authors have reported changes at the nutritional level [Narayana et al, 2018; Islam et al, 2020; Vigani et al, 2021], lipid composition [Islam et al, 2020] and gene expression. Interestingly, the speed of these responses suggests a first signaling stage that does not depend on gene expression [Narayana et al, 2018], even though several gene responses have been reported in response to a MF.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of signaling and metabolic processes in plants by the geomagnetic field is the subject of a growing number of studies [ 22 , 55 , 56 , 57 , 58 , 59 ]. In the introduction, we presented the background that the temperature growth responses of plants can also be modulated by the geomagnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…To study these effects, we built an exposure system made of a triaxial Helmholtz coils system of about 8 m 3 able to reduce the GMF from values of about 42,000 nT and inclination of about 58 • (average values in Italy) to Near Null MF (NNMF) values (about 30 nT) [34]. With this system, we already showed that plants differentially perceive MF variations in shoots and roots [35], with higher root oxidative stress responses [36], modulate ROS production and scavenging mechanisms [33], delay the transition to flowering, reduce leaf area index and flowering stem length and downregulate the flowering-related genes [34], alter clock gene amplitude [37], modulate gene expression pathways downstream of cryptochrome and phytochrome photoactivation [11], alter Fe and copper uptake efficiency and plant mineral nutrition [25,26] as well as lipid metabolism [38].…”
Section: Introductionmentioning
confidence: 97%
“…The expression of MagR and Cry genes has been demonstrated in different organisms [22,23] and was evaluated in the model plant Arabidopsis thaliana [24]. In this plant, the GMF affects the expression of iron-uptake genes under iron deprivation conditions and the simultaneous alteration of Fe-S availability [25]. Moreover, alteration of the GMF intensity affects Fe content and homeostasis [26].…”
Section: Introductionmentioning
confidence: 99%